Strategi Pelayanan Berbasis Customer Relationship Management (CRM) dalam Meningkatkan Loyalitas Penumpang : Studi Kasus pada Kapal Penumpang PT Pelni - Bagyo Dodo Munfarid; Syamsul Arifin; Nur Aini Anisa (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study was motivated by the increasing competition between sea transportation and other modes of transportation, such as air and land, which required PT PELNI as a state-owned shipping company to continuously develop service strategies capable of maintaining and enhancing passenger loyalty. In particular, the implementation of Customer Relationship Management (CRM) has become an important approach to improve the relationship between the company and passengers, ensuring service quality that meets expectations and fosters long-term engagement. The objectives of this study were to analyze the application of CRM strategies on PT PELNI passenger ships, identify factors influencing the effectiveness of CRM implementation, and assess its impact on passenger loyalty. A descriptive qualitative approach was employed, using in-depth interviews with passengers and staff, documentation of corporate policies and reports, as well as interactive data analysis to obtain a comprehensive understanding. The results indicate that CRM at PT PELNI has been fairly effective, particularly through improvements in service quality, staff professionalism, and the broad network of routes, which contribute to passenger satisfaction and loyalty. However, limitations were found in terms of service personalization, data utilization, and post-trip communication, signaling the need for digital-based loyalty programs and more integrated data management. The implications of this study highlight the importance of developing a more passenger-centric CRM strategy to strengthen long-term relationships, enhance customer retention, and support PT PELNI’s competitiveness in the maritime transportation industry.